Corporate Characteristics and International Financial Reporting Standards (IFRS) Compliance among Family-owned Listed Firms in Nigeria - OLATERU-OLAGBEGI, Adeparubi; ALADE, Muyiwa (The Journal of Accounting and Management, 2023)
The study investigated the effect of corporate characteristics on the International Financial Reporting Standards (IFRS) compliance of listed family-owned businesses in Nigeria. Secondary data were used to achieve the objective of the study. The population comprised thirty-seven family-owned firms listed in Nigeria Exchange Group as at 31st December, 2021. The study adopted purposive sampling technique to select thirty-three listed family-owned businesses based on at least 5 percent voting right, and data availability. Unbalanced panel data covering 2012 – 2021 were drawn for the purpose of analysis. The collected data were analyzed using descriptive and inferential statistics such as panel regression technique. The results showed that board gender diversity had positive effect on the level of IFRS compliance among the family-owned listed firms in Nigeria, and auditor-type significantly influence level of compliance with IFRS by the firms. Also¸ leverage of the firm had negative effect on the family-owned businesses’ extent of compliance with IFRS in Nigeria. The study concluded that corporate characteristics present significant effect on the IFRS compliance of family owned businesses in Nigeria. The study has policy implication for the accounting standard setters in Nigeria and globally, that is Financial reporting Council of Nigeria and International Accounting Standards Board (IASB).